(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Spent engine oil contaminated soil samples were collected and divided into three portions along with uncontaminated soil sample collected 10 meters away from the contaminated site. Two of the contaminated soil samples were treated with 0.5M NaOH and heat at 2500C respectively. All the samples were extracted with appropriate solvents using sonication, cleaned up and then analyzed with gas chromatograph coupled to flame ionization detector. The results show that total PAHs concentration of contaminated soil sample was 333.6820 mg/kg, contaminated soil sample treated with 0.5M NaOH, 104.8540 mg/kg, contaminated soil sample treated with heat at 2500C was 180.0905 mg/kg and the uncontaminated soil sample, 0.7084 mg/kg. The results showed that Wukari mechanic village is contaminated with PAHs through indiscriminate disposal of spent engine oil. Furthermore, treatment with 0.5M NaOH was a more effective means of remediation relative to treatment with heat at 250oC for two hours. The study will be an appropriate guide for the artisans following enlightenment about the possible threat that contact with PAH contaminated soils could have on their health.